Cyberbullying Victimization, Self-Esteem and Suicidal Ideation in Adolescence: Does Emotional Intelligence Play a Buffering Role? - Extremera, Natalio; Quintana-Orts, Cirenia; Mérida-López, Sergio; Rey, Lourdes (Frontiers in Psychology, 2018)
Cyberbullying has been linked to social, physical and psychological problems for adolescent victims but there has been no analysis of the specific role of emotional intelligence in protecting against the negative symptoms associated with cyberbullying victimization. This study examined the interaction between cyberbullying victimization and emotional intelligence (EI) as predictors of psychological maladjustment (operationalized as high suicidal ideation and low self-esteem) in 1,660 Spanish adolescents. We also investigated whether levels of EI moderated the relationship between cyberbullying victimization and mental health problems. The cyberbullying victimization x EI interaction contributed to variance in suicidal ideation and self-esteem in our sample of adolescent victims. Adolescent victims of cyberbullying with high EI scores reported lower suicidal ideation and higher self-esteem than their less emotionally intelligent counterparts. Thus, our data provide empirical support for theoretical and conceptual work connecting victimization, EI abilities and mental health associated with cyberbullying. This suggests that alone, but also in combination, EI may be particularly relevant in leading to increased levels of mental health issues in cyberbullying victims. Finally, the theoretical implications of our findings on the relationship between these variables and the mental health issues of adolescent victims of cyberbullying are discussed.